2009
DOI: 10.1007/s00277-009-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hepatitis B virus following rituximab-based regimens: a serious complication in both HBsAg-positive and HBsAg-negative patients

Abstract: Hepatitis B virus (HBV) reactivation is a well-known complication of lymphoma treatment in the pre-rituximab era. This complication has not been as well studied, however, since monoclonal anti-CD20 antibody became the standard regimen for B cell lymphoma. In this retrospective study, 115 B cell lymphoma patients who received rituximab-containing therapy were analyzed. Of 15 hepatitis B surface antigen (HBsAg)-positive patients, five received lamivudine prophylaxis and did not develop HBV-related hepatitis duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 36 publications
5
124
1
5
Order By: Relevance
“…(HEPATOLOGY 2015;62:387-396) 4 The incidence of HBV reactivation in patients with lymphoma and resolved hepatitis B after rituximab-based therapy ranges from 1.5% to 23.8%. [5][6][7][8] Reactivation of HBV infection in cancer patients receiving chemotherapy may cause interruption of chemotherapy and, in severe cases, lead to liver failure and death. 9-11 Additionally, the prognosis of cancer may be compromised by disruption in anticancer treatment Abbreviations: ALT, alanine aminotransferase; anti-HBc, antibody to hepatitis B core antigen; CI, confidence interval; HBsAg, hepatitis B surface antigen; HBV, hepatitis B virus; HCC, hepatocellular carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(HEPATOLOGY 2015;62:387-396) 4 The incidence of HBV reactivation in patients with lymphoma and resolved hepatitis B after rituximab-based therapy ranges from 1.5% to 23.8%. [5][6][7][8] Reactivation of HBV infection in cancer patients receiving chemotherapy may cause interruption of chemotherapy and, in severe cases, lead to liver failure and death. 9-11 Additionally, the prognosis of cancer may be compromised by disruption in anticancer treatment Abbreviations: ALT, alanine aminotransferase; anti-HBc, antibody to hepatitis B core antigen; CI, confidence interval; HBsAg, hepatitis B surface antigen; HBV, hepatitis B virus; HCC, hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…4 The incidence of HBV reactivation in patients with lymphoma and resolved hepatitis B after rituximab-based therapy ranges from 1.5% to 23.8%. [5][6][7][8] Reactivation of HBV infection in cancer patients receiving chemotherapy may cause interruption of chemotherapy and, in severe cases, lead to liver failure and death. [9][10][11] Additionally, the prognosis of cancer may be compromised by disruption in anticancer treatment during the course of hepatitis, with a delay in treatment cycles and premature termination of chemotherapy.…”
mentioning
confidence: 99%
“…More than one-third of the world's population has been infected with the HBV and there are 350 million people with chronic infection; 75% of them live in Southeast Asia and the Western Pacific regions 1,2 . There is a chance of reactivation of a previous HBV infection in patients undergoing chemotherapy or immunosuppressive therapy for rheumatism, malignancies, autoimmune hepatitis, and systemic lupus erythematosus (SLE); this reactivation is a major cause of morbidity and mortality 3 .…”
Section: Reactivation Of Hepatitis B Virus After Steroid Treatment Inmentioning
confidence: 99%
“…Recent development of the prophylactic use of antiviral agents against HBV has made screening and monitoring of HBV status essential in patients with rheumatic diseases who are starting glucocorticoids, to ensure adequate prophylaxis and/or preemptive therapy for reactivation 2,12 . We describe the cases of 2 patients taking glucocorticoids for rheumatic diseases without timely prophylactic treatment of nucleoside analog against HBV reactivation.…”
Section: Reactivation Of Hepatitis B Virus After Steroid Treatment Inmentioning
confidence: 99%
“…It is typically exposed in the majority of patients with the positivity of antibody against HBV core antigen (anti-HBc) (25,31) . It has been demonstrated that 20% of occult HBV infections are negative for all HBV serological markers, even though the number of HBV DNA was found four, the HBV viral load was generally low (28) . This finding suggests that the diagnosis of OBI can be difficult due to the very low amounts of viral DNA (<200 IU/mL) in the infected persons without detectable HBsAg (35) .…”
Section: Introductionmentioning
confidence: 99%